2012
DOI: 10.4067/s0370-41062012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Reemplazo renal en el post-operatorio de niños sometidos a cirugía cardíaca con circulación extracorpórea

Abstract: Renal replacement therapy after cardiac surgery with extracorporeal circulation Objective: Acute kidney injury (AKI) is a frequent complication of cardiac surgery with cardiopulmonary bypass (CPB). The aim of this study was to determine the incidence of renal replacement therapy (RRT) requirement in children undergoing surgical repair for congenital cardiopathies and identify the risk factors for requiring RRT. Patients and Methods: A retrospective, descriptive study was performed. The records of patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
6
1
1
Order By: Relevance
“…A research (24) carried out in Chile, reported that the incidence of RRT in the postoperative period of cardiac corrections with ECC was lower than that reported in other studies (31)(32)34) . However, it highlighted the implementation of ultrafiltration at the end of ECC in almost all patients, which facilitated strict volume control in the postoperative period and reduced the need for RRT due to hypervolemia.…”
Section: -Emerging Strategies In Child Health Care In the Postoperative Period Of Cardiac Surgerymentioning
confidence: 66%
See 3 more Smart Citations
“…A research (24) carried out in Chile, reported that the incidence of RRT in the postoperative period of cardiac corrections with ECC was lower than that reported in other studies (31)(32)34) . However, it highlighted the implementation of ultrafiltration at the end of ECC in almost all patients, which facilitated strict volume control in the postoperative period and reduced the need for RRT due to hypervolemia.…”
Section: -Emerging Strategies In Child Health Care In the Postoperative Period Of Cardiac Surgerymentioning
confidence: 66%
“…Among the complications associated with the postoperative period of CHD, the most prevalent is Acute Renal Insufficiency (ARI). This does not depend on the technological advances of ECC, as well as the procedures in the intra and postoperative period, corresponds to a high rate of postoperative morbidity and mortality (30) , with reported incidence between 17 and 72% (24) .…”
Section: -Emerging Strategies In Child Health Care In the Postoperative Period Of Cardiac Surgerymentioning
confidence: 92%
See 2 more Smart Citations
“…De los varios modelos animales de lesión renal aguda, la isquemia reperfusión renal es uno de los más comúnmente estudiados porque es reproducible y se puede graduar fácilmente la magnitud de la lesión. Además tiene implicancia clínica en cirugía cardíaca con clampeo aórtico, transplante renal, nefrectomía parcial, paro cardíaco, entre otros [5][6][7][8] .…”
Section: Lesión Renal Agudaunclassified